ANALYSIS OF NONLINEAR TRANSIENT DYNAMIC RESPONSE FOR EXPLOSION-PROOF BOX - LIU XiaoDong; JIN BinBin; ZHU Danan (Jixie qiangdu)
Explosion-proof box is used for the protection of petroleum drilling equipment. Costly explosion experiments will be avoided and the development cycle will be greatly reduced if finite element method is chosen for the analysis of explosion-proof performance. Completed the transient dynamic response analysis in nonlinear material model based on MSC Nastran SOL400 module. Do the checking after we got various parts’ behavior of explosion-proof box under blast shock. The results could be the reference of explosion-proof box’s design or structural optimization.